Employee Performance in terms of Compensation and Work Motivation - Aletta Dewi Maria (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to determine and analyze the effect of compensation and work motivation on employee performance at Santika Pekalongan Hotel. The population of this study were employees of the Santika Pekalongan hotel with a total of 73 respondents. The sampling technique in this study used a census. This analysis includes validity, reliability, multiple linear analysis, t test, f test, coefficient of determination analysis. The results of this study indicate that compensation (X1) has a positive but not significant effect on employee performance, work motivation (X2) has a positive and significant effect on employee performance